Attitudes toward disabilities among students in college settings: A multidimensional scaling analysis with biplot. Issue 2 (18th October 2019) - Tu, Wei-Mo; Yan, Min-Chi; Li, Qiwei; Watts, Justin
Abstract: We investigated attitudes toward 10 specific groups of individuals with disabilities among students in college settings. These groups comprised major depression, substance use disorder (SUD), anxiety disorder, autism spectrum disorder (ASD), cerebral palsy, hearing impairment, learning disability, visual impairment, spinal cord injury, and cancer survivor. The multidimensional scaling (MDS) analysis revealed a two-dimension space representing participants' attitudes toward those disabilities. The MDS biplot further indicated higher levels of perceived dangerousness from the groups with SUD, major depression, anxiety disorder, and ASD. The hierarchical cluster analysis revealed that cluster A (SUD and major depression) was rated as having the highest level of social distance (i.e., negative attitudes). The implications for research and practice in rehabilitation counseling were discussed.